Entangled Life
VI, 279 p. 15 illus.
Keywords: This volume explores the interactions between organisms and their environments and how this “entanglement” is a fundamental aspect of all life. It brings together the work and ideas of historians, philosophers, biologists, and social scientists, uniting a range of new perspectives, methods, and frameworks for examining and understanding the ways that organisms and environments interact. The volume is organized into three main sections: historical perspectives, contested models, and emerging frameworks. The first section explores the origins of the modern idea of organism-environment interaction in the mid-nineteenth century and its development by later psychologists and anthropologists. In the second section, a variety of controversial models—from mathematical representations of evolution to model organisms in medical research—are discussed and reframed in light of recent questions about the interplay between organisms and environment. The third section investigates several new ideas that have the potential to reshape key aspects of the biological and social sciences. Populations of organisms evolve in response to changing environments; bodies and minds depend on a wide array of circumstances for their development; cultures create complex relationships with the natural world even as they alter it irrevocably. The chapters in this volume share a commitment to unraveling the mysteries of this entangled life.